Of Ice and Men: Chilling leadership tales of four great explorers - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2011)
Four great names with four different temperaments; four different fates but one common passion: the honour of conquering the icy frontiers of the North and South. Having documented the experiences of four 19-20th century Norwegian and British explorers, author Ragnar Kvam shares stories from those expeditions at a SMU Wee Kim Wee Centre talk – tales of what leadership ought not to be.